LEGAL PROTECTION OF ADOPTED CHILDREN BETWEEN COUNTRIES IN THE PERSPECTIVE OF INTERNATIONAL CIVIL LAW - Cindy Atika Zulaeka; Rina Arum Prastyanti (Cahaya Ilmu Bangsa, 2024)
Inter-state child adoption is a complex global phenomenon with various legal and social aspects. This research aims to provide an in-depth analysis of the international civil law framework governing international child adoption, with a focus on the legal protection of adopted children. This research employs a normative legal research method to comprehensively examine various relevant national and international laws, regulations, and legal theories developed in this field and to analyze the legal protection of interstate child adoptions from an international civil law perspective. This review takes a closer look at the legal protection of intercountry child adoptions under international civil law. The focus is on analyzing the vulnerability of children in the context of international adoption and the international community's efforts to protect their rights. The review is conducted through an analysis of relevant national and international laws as well as relevant legal literature.